Kajian Molekuler Layu Buah Muda Kakao (Theobroma cacao L.): Ekspresi TcPIN1 Like Gene - Yohana Theresia Astuti; Kumala Dewi; Santosa Santosa; A. Adi Prawoto (Universitas Atma Jaya Yogyakarta, 2010)
This experiment was carried out to evaluate the expression of TcPIN1 like gene in cocoa (Theobroma cacao L.). DNA and RNA were extracted from 7 weeks old of both healthy and cherelle wilt cocoa pods. PCR was done with two primer set based on PIN1 sequenced of Arabidopsis. Primer PIN1-1: Forward: taaggtgatgccaccaacaa; Reverse: gccatgaacaacccaagact. Primer PIN!-2: Forward: tttgtgtggagctcaagtgc; Reverse: ctgcgtcgttttgttgctta. RT-PCR was done with primer PIN1-2. The results showed that TcPIN1-2 like gene was found in healthy young pods, but not availabe in cherelle wilt pods of cocoa.